Modelling crop water footprint and virtual water flow in the Yellow River Basin using the SWAT model - ZI Tiantian; LIU Jing; XUAN Keyang (Guan'gai paishui xuebao)
【Objective】 The Yellow River Basin, the second largest in China, plays a crucial role in food production in the country. In this paper, we analyze the spatiotemporal variations in agricultural water use efficiency and calculate water resource flow patterns and their optimal allocation at watershed scale in the basin. 【Method】 Using the SWAT model, the basin was divided into sub-basin units to calculate crop water footprints. Virtual water flows were analyzed using social equity principles and the gravitational force method. 【Result】In 2020, the total crop water footprint in the basin was 76.91 billion m3, with green water accounting for 69.7%. The middle reaches contributed the largest to the total water footprint, significantly surpassing upstream and downstream regions. Both blue and green water footprints exhibited seasonal variation, peaking between May and August. The average water footprint for crop production was 0.72 m3/kg, with notable spatial differences: high in the Northern regions and low in the South. High blue water footprints were predominantly in the upper and middle reaches. The total virtual water flow associated with crop production was 19.15 billion m3, with green water flow exceeding blue water flow. The Northern regions served as virtual water exporters, while the Southern regions were net importers.【Conclusion】Effective management of green water resources is essential for sustainable water use in the Yellow River Basin. Special attention is required for the middle reaches due to their higher water consumption. Key strategies include prioritizing irrigation water allocation in the regions with low blue water footprints, optimizing crop planting structures, adopting water-saving technologies, and establishing compensation mechanisms for virtual water flow. These measures will promote the sustainable utilization of water resources throughout the basin.